Junk : digging through America's love affair with stuff - Stewart, Alison, 1966- (Chicago Review Press, 2016)
"Junk has become ubiquitous in America today. Who doesn't have a basement, attic, closet, or storage unit filled with stuff too good to throw away? Or, more accurately, stuff you think is too good to throw away. When journalist and author Alison Stewart was confronted with emptying her late parents' overloaded basement, a job that dragged on for months, it got her thinking: How did it come to this? Why do smart, successful people hold on to old Christmas bows, chipped knick-knacks, VHS tapes, and books they would likely never reread? She discovered she was not alone. Junk details Stewart's three-year investigation into America's stuff, lots and lots and lots of stuff. Stewart rides along with junk removal teams from around the country such as Trash Daddy, Annie Haul, and Junk Vets. She goes backstage to a taping of Antiques Roadshow, and learns what makes for compelling junk-based television with the executive producer of Pawn Stars. And she even investigates the growing problem of space junk--23,000 pieces of manmade debris orbiting the planet at 17,500 mph, threatening both satellites and human space exploration. But it's not all dire. There are creative solutions to America's overburdened consumer culture. Stewart visits with Deron Beal, founder of FreeCycle, an online community of people who would rather give away than throw away their no-longer-needed possessions. She spends a day at a Repair Cafe, where volunteer tinkerers bring new life to broken appliances, toys, and just about anything. Stewart also explores communities of "tiny houses" without attics and basements in which to stash the owners' trash. Junk is a delightful journey through 250-mile-long yard sales, and packrat dens, both human and rodent, that for most readers will look surprisingly familiar"--